Glokaya Kuzdra - Bagina, Elena (project baikal, 2017)
Inclusion of historical buildings or their fragments in a new development is not a novelty. During the last 10-15 years this method has been widely used. Such decisions are rooted in the field of economics and regulations for the protection of the historic development. Due to unprofessional solutions made by both architects and approving authorities the old is irreparably mutilated, while the new looks absurd.
Keywords: historic buildings; fragments; new development; unprofessional solutions